Pressure transient behaviour of a horizontal steam injection well in a naturally fractured reservoir - Yi, T.T. (Asian Research Publishing Network, 2018)
Naturally fractured reservoirs constitute majority of the reservoirs documented on earth. Tectonic activities on earth have produced widespread natural fractures which properties should be accounted for in reservoir simulation. The intrinsic properties of naturally fractured reservoirs make accurate simulation of the reservoir challenging and still have been a topic of discussion. Studying the pressure and pressure-derivative behaviour of a well has been proven in literature to be an accurate method for reservoir characterization and reservoir evaluation. The pressure transient behaviour of vertical and horizontal production wells has been well researched and presented in literature but little information exist on the pressure transient behaviour of a horizontal steam injection well in a naturally fractured reservoir. Therefore, this paper focuses on the pressure transient behaviour of a horizontal steam injection well in a naturally fractured reservoir to accurately characterize the reservoir. Simulation studies are conducted using Computer Modelling Group (CMG) software, STARS, a thermal recovery simulator. A base model of a horizontal steam injection well in a dual porosity reservoir is constructed and the pressure transient behaviour is studied through parameter variation. Results show that we can observe a radial flow regime, followed by a downward dip due to the gas injection, another downward dip due to the dual porosity storativity and finally pseudoradial flow due to the pressure transient reaching the boundary. The negative or close to negative pressure-derivative observed in the first downward is due to the high compressibility nature of steam. The presence of steam injection and the dual porosity may mask other flow regimes in the model and further test designs could be constructed in the future to further study the pressure transient behaviour of a horizontal steam injection well in a naturally fractured reservoir. Â© 2006-2018 Asian Research Publishing Network (ARPN).